SISTEM PAKAR MINAT DAN BAKAT ANAK DENGAN MULTIPLE INTELLIGENCES BERBASIS WEB PADA SDIT MUTIARA ISLAM DEPOK - Sri Sureni; Herlawati Herlawati; Hendra Supendar (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
Identifying talents of children as early as possible as parents will surely find it helpful because parents can directly lead and guide so that their interests and talents can flourish. So it is with the child, the child can explore talents honed better and also can fill the days in its path with an activity that is meaningful to him and certainly liked it. Therefore needed an expert system application that can help figure it out. Application of expert system is an expert system that created the interest and talents of children elucidation web-based. The system uses a forward search method (Forward Chaining) to determine the child's interests and talents. The theory used is the theory of multiple intelligences (Multiple Intelligences) by Professor Howard Gardner. Expert System Application Determination interest and Kids Talent is expected to help in knowing the interests and talents of children as early as possible. So with a system of this application, parents can maximize skill children, so that children can be multitalented.